Kajian Etis Teologis Terhadap Remaja yang Hamil di Luar Nikah - Tene, Jenifer P.; Arina, Hein (Educatio Christi, 2024)
This study aims to examine teenage pregnancy outside of marriage from the perspective of Christian Ethics. This research is based on the fact of the problem of teenagers who have many pregnancies outside of marriage. The purpose of this research is to find out the causes of out-of-wedlock pregnancy cases, the role of the church and the study of Christian ethics towards teenagers who are pregnant outside of marriage in the GMIM Imanuel Wanea congregation. This research was conducted using qualitative research. This research uses observation, interview and documentation techniques. Pregnancy cases outside of marriage are caused by sexual acts caused by promiscuity, the environment, mass media and lack of supervision from parents. From the research I conducted, it was found that the factors that cause teenagers to become pregnant outside of marriage are lack of parental attention, free sex, wrong association, being forced etc. For this reason, churches and parents need to be aware of the causes of pregnancy outside of marriage. For this reason, churches and parents need to be more involved in fostering and supervising the lives of teenagers towards activities such as their daily associations and activities.